2016
DOI: 10.1016/j.bandl.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Neural encoding of the speech envelope by children with developmental dyslexia

Abstract: HighlightsWe measure encoding quality of low-frequency speech envelopes by children using EEG.Encoding accuracy is significantly above chance for all groups.Accuracy is poorer in dyslexic children than younger RL-matched children.Individual differences in encoding accuracy are related to prosodic awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
173
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 161 publications
(201 citation statements)
references
References 67 publications
(101 reference statements)
22
173
3
3
Order By: Relevance
“…Our data are suggestive of functionally-atypical right-lateralised processing of slower temporal modulations in children with developmental dyslexia. Although the stimuli in the current study were non-speech, we were able to measure neural encoding of speech in the same sample of children in a later study, using semantically unpredictable noise-vocoded sentences (Power et al, 2016). Power et al (2016) utilised a reverse engineering approach, in which the speech envelopes of the sentences were estimated from the neural (EEG) response (via envelope reconstruction, a form of speech resynthesis, see O'Sullivan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our data are suggestive of functionally-atypical right-lateralised processing of slower temporal modulations in children with developmental dyslexia. Although the stimuli in the current study were non-speech, we were able to measure neural encoding of speech in the same sample of children in a later study, using semantically unpredictable noise-vocoded sentences (Power et al, 2016). Power et al (2016) utilised a reverse engineering approach, in which the speech envelopes of the sentences were estimated from the neural (EEG) response (via envelope reconstruction, a form of speech resynthesis, see O'Sullivan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in hemodynamic activity were also found for the left superior temporal gyrus and the left angular gyrus (areas classically considered to be active during speech processing, see Rauschecker & Scott, 2009). The hemodynamic responses were significantly related to rise time discrimination for this sample of children (these were the same children who had participated in Power et al, 2013Power et al, , 2016.…”
Section: Neural Entrainment To Slower Modulations In Speech and Nonmentioning
confidence: 94%
“…Hence, all the information in the linguistic hierarchy encoded by the listener that is carried by AM information (information about syllables, onset–rimes and phonemes), as well as prosodic linguistic information, would be of poorer quality. Subsequent to Power et al's () rhythmic repetition studies, TS theory has been investigated further in studies using sentences and stories (Molinaro, Lizarazu, Lallier, Bourguignon, & Carreiras, ; Power, Colling, Mead, Barnes, & Goswami, ). There are also relevant studies using the ASSR, described in the next section.…”
Section: Phase Entrainment To Rhythmic Speech In Developmental Dyslexiamentioning
confidence: 99%
“…The children had to repeat what they thought they heard. Power et al . reported that the speech envelopes in the 0–2 Hz (delta) band were encoded significantly less accurately by the brains of the children with dyslexia.…”
Section: Amplitude Rise Time Discrimination and Neural Entrainment Inmentioning
confidence: 99%